Bookish vocabulary in the texts of Ukrainian postmodern prose (a functional-stylistic aspect) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article presents the functional-stylistic features of social-political vocabulary and scientic-terminological lexicon which function in the texts of Ukrainian postmodern prose.
Keywords: social-political vocabulary; scientic-terminological lexicon; functional-stylistic features; Ukrainian postmodern prose